Safety and danger of biologic treatments in psoriasis in context of cutaneous T-cell lymphoma (CTCL) - Kołkowski, Karol; Sokołowska-Wojdyło, Małgorzata (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Microenvironment has a significant impact on the pathogenesis of cutaneous T-cell lymphoma (CTCL), especially in the context of new emerging biologic therapies. Our aim was to review the literature on interleukins 12, 17, 23 and tumour necrosis factor-a in mycosis fungoides in order to clarify the safety of using biologics in the treatment of psoriasis. Our analysis suggests that these drugs may have an impact on the progression of CTCL. Concluding, in case of uncertain psoriatic lesions, a biopsy followed by pathologic examination should exclude the possibility of co-existence of a primary cutaneous lymphoma before administration of therapies affecting cytokine profiles.